Continuity and mutability of dual occupational profiles – the contribution of regulatory work - Conein, Stephanie [Verfasser]; Hackel, Monika [Verfasser]; Bretschneider, Markus [Verfasser] (My University, 2021)
"“The vocational education and training system is in crisis!” The reasons for such statements are multifarious in nature, but they regularly cause and have caused existing structures and VET regulatory work in particular to be called into question. A memorandum produced by DIETER EULER and ECKART SEVERING in the autumn of 2020 was one such example. Against this background, the present article provides insights into the regulatory work conducted by BIBB and shows how consensual cooperation serves as a vehicle for the successful development of occupations in the field of tension between continuity and change. The article also clarifies how regulatory work recognises developments at an early stage, integrates them into training occupations in a timely manner, and structures these occupations in a way that enables training to take place over the long term and across a broad basis." (authors' abstract; BIBB-Doku)
Kontinuität und Wandlungsfähigkeit dualer Berufsbilder – der Beitrag der Ordnungsarbeit
Keywords: S 2.2 Ordnungen & Ordnungsverfahren; S 2.2.2.1 Ausbildungsordnungen; S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); 370; Ordnung von Ausbildungsberufen; Ausbildungsordnung; Ordnungspolitik; Zukunft der Arbeit; sozialer Wandel; Bundesinstitut für Berufsbildung